Terahertz Néel spin-orbit torques drive nonlinear magnon dynamics in antiferromagnetic Mn2Au - Behovits, Yannic; Chekhov, A. L.; Bodnar, Stanislav; Gueckstock, O.; Reimers, S.; Lytvynenko, Y.; Skourski, Y.; Wolf, M.; Seifert, T. S.; Gomonay, O.; Kläui, M.; Jourdan, M.; et al. (Nature Communications, 2023)
Antiferromagnets have large potential for ultrafast coherent switching of magnetic order with minimum heat dissipation. In materials such as Mn2Au and CuMnAs, electric rather than magnetic fields may control antiferromagnetic order by Néel spin-orbit torques (NSOTs). However, these torques have not yet been observed on ultrafast time scales. Here, we excite Mn2Au thin films with phase-locked single-cycle terahertz electromagnetic pulses and monitor the spin response with femtosecond magneto-optic probes. We observe signals whose symmetry, dynamics, terahertz-field scaling and dependence on sample structure are fully consistent with a uniform in-plane antiferromagnetic magnon driven by field-like terahertz NSOTs with a torkance of (150 ± 50) cm2 A−1 s−1. At incident terahertz electric fields above 500 kV cm−1, we find pronounced nonlinear dynamics with massive Néel-vector deflections by as much as 30°. Our data are in excellent agreement with a micromagnetic model. It indicates that fully coherent Néel-vector switching by 90° within 1 ps is within close reach.
Gesehen am 17.05.2024